Janus Ag/Fe-HfO2 nanoparticles for enhanced radio-photothermal tumor therapy via magnetic resonance imaging and multienzyme activity - Xinying Liu; Baohui Liu; Conglong Chen; Chaowei Hong; Jia Xu; Yixuan Ruan; Ling Huang; Shanni Hong; Wei Chen; Ye Kuang (Materials Today Bio)
A significant challenge in modern radiotherapy (RT) is to minimize the detrimental effects on adjacent healthy tissues while concurrently increasing the susceptibility of tumor tissue to radiation. Investigating nanoradiosensitizers with multifunctional properties has a lot of potential as a highly effective strategy for augmenting the efficacy of RT. A novel Janus Ag/Fe-HfO2 nanoparticle was synthesized in a single-step process. This versatile nanoradiosensitizer combines photothermal capabilities, enzyme-like activities, and the capacity for magnetic resonance imaging (MRI). The surfaces have been meticulously engineered with PEG to boost biocompatibility and adorned with RGD-targeting peptides that selectively target tumor cells (Ag/Fe-HfO2-PEG-RGD). The characterization results have demonstrated the successful preparation of Janus Ag/Fe-HfO2 nanoparticles with a diameter of roughly 10 nm. Furthermore, the photothermal properties, MRI ability, and enzymatic catalytic activities (generate O2, produce hydroxyl radical, and consume GSH) of Ag/Fe-HfO2-PEG-RGD were verified in vitro experiments. In vivo experiments, by integrating T1-weighted MRI-guided RT with the enzymatic activities of these nanoparticles, along with the application of photothermal heating, we have achieved a synergistic enhancement in the therapeutic efficacy of RT. Moreover, it stimulates tumor-specific immune responses, leading to an increased presence of tumor-infiltrating CD8+ T cells. This integrated multimodal nanotherapeutic platform, which capitalizes on the potent enhancement of RT effects, offers a promising new strategy in the ongoing battle against cancer.